(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Investigation of the spatial contrast sensitivity (CS) after cataract surgery can more accurately assess the quality of the received vision functions. The purpose — to carry out a comparative analysis of CS in patients with implanted IOL of 5 different models. Materials and methods. Studies were conducted in mesopic andphotopic conditions at low, medium and high spatial frequencies in different postoperative periods. Groups were formed according to the implanted IOL model — SA60AT, AOMI60, Tecnis ®, SN60WFand SL-907Centrix DZ. Results and discussion. The study of CS values showed the advantage of IOL SL-907 Centrix DZ in all postoperative periods in mesopic (on average from 0.7 to 2.2 db (4.8-16.0 %)) and photopic (from 0.6 to 1.7 db (3,6-10,1 %), respectively) conditions (p < 0,05) at low and medium spatial frequencies. CS values in the high spatial frequencies were the same for all types of lenses. CS values were higher in the medium spatial frequencies compared to the low spatial frequencies average of 1.1 db (7.5 %) for all patients, but the highest degree was noted in the group with IOL SL-907 Centrix DZ — 1.2 db (7.4 %). Conclusions. IOL SL-907 Centrix DZ has better CS indices compared to other models that allows to recommend it for wide application in cataract surgery for the purpose of better personalization in IOL model selecting for implantation.